2016
DOI: 10.1007/s00392-016-1028-3
|View full text |Cite
|
Sign up to set email alerts
|

Aortic events in a nationwide Marfan syndrome cohort

Abstract: More than a third of MFS patients experienced an aortic event and male patients had significantly more aortic events than females. More than half of the total number of dissections was in patients undiagnosed with MFS at the time of their event. This emphasizes that diagnosing MFS is lifesaving and improves mortality risk by reducing the risk of aorta dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 33 publications
2
52
2
1
Order By: Relevance
“…There is a predominance of first time aortic events in men in the age group from 20 to 30 years. Previous studies have also shown that aortic events occur earlier in men than women (Detaint et al, 2010;Faivre et al, 2007;Groth et al, 2017;Rand-Hendriksen et al, 2009). The reason for the gender differences of men undergoing aortic surgery at a younger age, parallel to a shortened life expectancy, is not known.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…There is a predominance of first time aortic events in men in the age group from 20 to 30 years. Previous studies have also shown that aortic events occur earlier in men than women (Detaint et al, 2010;Faivre et al, 2007;Groth et al, 2017;Rand-Hendriksen et al, 2009). The reason for the gender differences of men undergoing aortic surgery at a younger age, parallel to a shortened life expectancy, is not known.…”
Section: Discussionmentioning
confidence: 96%
“…Other conditions, such as valvular heart disease and myocardial dysfunction with arrhythmias are also known as causes of premature death in MFS (Yetman, Bornemeier, & McCrindle, 2003). Some studies indicate that men experience aortic diseases at younger age than women with MFS (Detaint et al, 2010;Groth et al, 2017;Rand-Hendriksen et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, we found that only about 35% of patients with aortic dissection were female, which was not different for patients with Marfan syndrome compared to those without, despite the higher incidence of pregnancy-associated dissection in Marfan syndrome. Recently published data from a Danish national registry of Marfan syndrome patients confirm that male patients have a 75% higher risk of an aortic event than female patients at any given age (9). Aortic dilatation does not appear to be more prevalent in male than in female adolescents with Marfan syndrome (10).…”
Section: Perspectivesmentioning
confidence: 99%
“…The first mechanism is the occurrence of spinal cord infarct as a complication of aortic surgery or dissection. Indeed, more than one third of patients with Marfan syndrome will be operated on an aortic event in their life (aortic dissection or preventively in aortic dilation [5]). Even if morbidity during this surgery decreases with novel techniques, spinal cord infarct is still one of their complications [6] and Marfan syndrome is a predictor of its occurrence [7].…”
Section: Discussionmentioning
confidence: 99%